Formulasi dan Evaluasi Floating System Tablet Difenhidramin HCl Menggunakan Kombinasi Matriks HPMC K4M dan Na. CMC - Khusnul Berty Indartantri; Noval Noval; Husda Oktaviannoor (Jurnal Surya Medika (JSM), 2021)
A floating system tablet was made using HPMC K4M and Na matrices. CMC with the active substance diphenhydramine HCl, which absorption in the stomach. The research aims to determine the effect of a combination of HPMC K4M and Na. CMC matrices are optimal in a floating system formulation. This research used an experimental method with a RAL design. Tablets were made by direct compression and were evaluated. The results were then analyzed statistically using One Way ANOVA. The loss results on the drying test, the tapped density test, and the measurement of the angle of repose of all formulations met the requirements. The powder flow rates of all formulations did not meet the requirements. The resulting tablet is white, bitter, round, and smells of medicine. Tablets in all formulations have uniform weight according to requirements. The hardness test results showed that only formulation 3 met the requirements, while all formulations did not meet the requirements in the friability test. In the lag time test, the results obtained in formulation 1 and formulation 2, formulation 3, and formulation 4 are 4 seconds, 4 seconds, 3 seconds, and 1 second. In contrast, the floating time results show that all formulations can float for 24 hours. All evaluation results indicate that the optimal formulation in formulation 3.